Why Planck (the Satellite) could have been Zel'dovich. Issue Volume 11:Issue S308(2015) (12th October 2016) - Partridge, Bruce
Abstract: In this brief paper, I cannot provide an overall review of the Planck results to date. Instead I will focus on a handful of results from both Planck and related cosmic microwave background (CMB) experiments that reflect Ya. B. Zel'dovich's legacy in cosmology. These include the Sunyaev-Zel'dovich effect in clusters of galaxies and in the cosmic web, and a map of the overall distribution of mass in the Universe derived from CMB maps.